Justicia prachuapensis, a new name for J. hansenii Rueangs. & Chantar. (Acanthaceae), a later homonym - Rueangsawang, Kanokorn; Chantaranothai, Pranom; Simpson, David A. (Phytotaxa, 2014)
A new name, Justicia prachuapensis, is proposed for an inadvertently created later homonym, J. hansenii Rueangs. & Chantar. (2013), non Silvar. & P. Mathew (1989).